2018
DOI: 10.1088/1748-0221/13/01/c01006
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness study of semi-insulating GaAs detectors against 5 MeV electrons

Abstract: A radiation hardness study of Semi-Insulating (SI) GaAs detectors against 5 MeV electrons is described in this paper. The influence of two parameters, the accumulative absorbed dose (from 1 to 200 kGy) and the applied dose rate (20, 40 or 80 kGy/h), on detector spectrometric properties were studied. The accumulative dose has influenced all evaluated spectrometric properties and also negatively affected the detector CCE (Charge Collection Efficiency). We have observed its systematic reduction from an initial 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Detectors investigated in this paper are the same samples as those studied and described in our previous papers [8][9][10][11][12]. The Schottky barrier detectors were made of a bulk VGF (Vertical Gradient Freeze) SI GaAs grade of 230 µm thickness with the circular Schottky electrode made of Ti/Pt/Au (10/35/90 nm) multilayer on the top and a whole area quasi-ohmic metal electrode from Ni/AuGe/Au (30/50/90 nm) multilayer on the back side of the substrate.…”
Section: Detector Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…Detectors investigated in this paper are the same samples as those studied and described in our previous papers [8][9][10][11][12]. The Schottky barrier detectors were made of a bulk VGF (Vertical Gradient Freeze) SI GaAs grade of 230 µm thickness with the circular Schottky electrode made of Ti/Pt/Au (10/35/90 nm) multilayer on the top and a whole area quasi-ohmic metal electrode from Ni/AuGe/Au (30/50/90 nm) multilayer on the back side of the substrate.…”
Section: Detector Characterisationmentioning
confidence: 99%
“…Si; GaAs detectors achieve higher detection efficiency of γ-and X-rays. There are only a few studies dealing with radiation resistance of GaAs detectors against high-energy electrons [6][7][8][9][10][11][12], however they present promising results. Afanaciev et al irradiated the Cr-doped GaAs sensors by 10 and 8.5 MeV electron beam at a dose rate of 20 to 400 kGy/h to a total dose of 1.5 MGy and observed the charge collection efficiency (CCE) degradation with the absorbed dose [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the ability of GaAs detectors to withstand doses of a few MGy when degraded by MeV electrons with the main limiting factor which is the charge collection efficiency decreasing with overall dose [13][14][15][16][17][18]. On the other hand, we have observed an improvement of the detection efficiency after initial detector degradation by 5 MeV electrons up to doses of 200 kGy [13] when measuring both the gamma as well as the alpha particle spectra of 241 Am. This phenomenon was explained by an assumed expansion of the active detector volume.…”
Section: Introductionmentioning
confidence: 61%
“…In this paper we evaluate the alpha particle spectra of 241 Am measured with the same semiinsulating GaAs detectors described in [13] but degraded by 5 MeV electrons up to 2 MGy doses. The detection efficiency is evaluated by integrated counts in the peak of the measured spectra.…”
Section: Introductionmentioning
confidence: 99%